Paradigma Islamisasi dan Integralisme Pendidikan Islam - Nurhadi Nurhadi (FONDATIA, 2019)
Education is the main pillar of the rise of a country and nation. The ideology and paradigm of thought of educational leaders are the life of the world of educational effectiveness in a country. Islam is a strict teaching about education with the term compulsory education from buayan to grave. The education cycle starts from the mother's womb (womb) to the soil content (barzah). These three natural linkages make Muslim thinkers who are concerned about education that links between the three realms (womb, world and barzah). The integralism paradigm of education emerged which tried to incorporate the values of revelation and sunnah in the world of education, both science and technology. No less important is the education thinker who connects science and technology with imtaq (Islamization). These two terms gave birth to new institutions in the world of education. The integralism paradigm includes religious values in science and technology, giving birth to religious education institutions with nuanced science and technology, for example modern Islamic schools (MIM) or Global MI (MIG), International MI (MII), and others. Likewise, the paradigm of Islamization of education gave birth to educational institutions that connected science and technology with imtaq, for example integrated Islamic elementary schools and tahfizd (SDIT and SDITh) and the like. Basically the two ideologies of thought have the same substance, but the effects that are different from each other, namely MIG, MIM and MII become as if they were public schools, while SDIT seems like a religious school. In substance, these two educational institutions do not violate the legislation concerning the national education system from the point of view of education, but ideologically both can be said to be the psimism of educational science. According to the authors both must be equated scientifically and the legality and formality. But in the view of Islamic education MI is more important than SDIT.